Get seen : online video secrets to building your business - Garfield, Steve (New rules of social media series., 2010)
The era of online video has arrived--now make it work for your business. In the last year, the world of online video exploded. Hollywood got into the game, professional actors and writers joined in, and independent producers looked to find their niche. Now, companies are wide awake to the opportunities for product and brand promotion as well as customer engagement. So how do you want to fit into the new online video universe?. The must-have guide, Get Seen by Steve Garfield, the "Paul Revere of video blogging," offers a quick and complete toolkit to get you up to speed on the latest that online.